PENDEKATAN PASTORAL KONSELING DAN PERAN GEREJA BAGI KAUM LGBT - Takalamingan, Joiske; Mangali, Agrendi (LIMMUD: Jurnal Ilmu Keagamaan dan Sosial Humaniora, 2025)
This study aims to explain the importance of the church's role for LGBT people and the importance of a pastoral counseling approach for LGBT people. The study used a descriptive qualitative method to analyze the role of the church and its patoral counseling role for LGBT people. This study found that the church's role in addressing LGBT people is limited and there is no pastoral counseling approach. Therefore, it is recommended that the church use a pastoral counseling approach in dealing with LGBT people to minimize dispaities whitin the church.